PENGARUH PENAMBAHAN SARI BUAH NANAS terhadap MUTU MINUMAN JELLY CINCAU - Piranti, Alde; Johan, Vonny Setiaries; Ali, Akhyar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this study were to determine the quality and the best formulation of cincau jelly drink with addition of pineapple extract. This study used a Complete Randomized Design consisting of five treatments and three replications to obtain fifteen experimental units. The treatments in this study were CN1 (cincau extract 90% and pineapple extract 10%), CN2 (cincau extract 80% and pineapple extract 20%), CN3 (cincau extract 70% and pineapple extract 30%), CN4 (cincau extract 60% and pineapple extract 40%), and CN5 (cincau extract 50% and pineapple extract 50%). The data obtained using the analysis of variance followed by Duncan’s New Multiple Range Test (DNMRT) at 5% level. Result of variance indicated that the ratio of grass jelly extract and pineapple extract at different concentration have significant effected on the content of sucrose concentration, pH, viscosity, color, flavor, texture, and overall assesment of hedonic jelly drinks produced. The best treatment was CN5 (cincau extract 50% and pineapple extract 50%), with sucrose concentration 21.09%, pH 4.36, viscosity 12175.30 cP, and description color was brownish green, scented pineapple, pineapple taste, slightly chewy texture, and overall rated liked by the panelists with a score 4.16.Keywords: cincau, pineapple, and jelly drink